OMIP‐93: A 41‐color high parameter panel to characterize various co‐inhibitory molecules and their ligands in the lymphoid and myeloid compartment in mice - Brandi, Johannes; Wiethe, Carsten; Riehn, Mathias; Jacobs, Thomas (Cytometry. Part A, 2023)
This 41‐color panel has been designed to characterize both the lymphoid and the myeloid compartments in mice. The number of immune cells isolated from organs is often low, whilst an increasing number of factors need to be analyzed to gain a deeper understanding of the complexity of an immune response. With a focus on T cells, their activation and differentiation status, as well as their expression of several co‐inhibitory and effector molecules, this panel also allows the analysis of ligands to these co‐inhibitory molecules on antigen‐presenting cells. This panel enables deep phenotypic characterization of CD4+ and CD8+ T cells, regulatory T cells, γδ T cells, NK T cells, B cells, NK cells, monocytes, macrophages, dendritic cells, and neutrophils. Whilst previous panels have focused on these topics individually, this is the first panel to enable simultaneous analysis of these compartments, thus enabling a comprehensive analysis with a limited number of immune cells/sample size. This panel is designed to analyze and compare the immune response in different mouse models of infectious diseases, but can also be extended to other disease models, for example tumors or autoimmune diseases. Here, we apply this panel to C57BL/6 mice infected with Plasmodium berghei ANKA, a mouse model of cerebral malaria.